2011
DOI: 10.1002/er.1938
|View full text |Cite
|
Sign up to set email alerts
|

Study on a novel solid oxide fuel cell/gas turbine hybrid cycle system with CO2 capture

Abstract: SUMMARYA novel solid oxide fuel cell (SOFC)/gas turbine (GT) hybrid cycle system with CO 2 capture is proposed based on a typical topping cycle SOFC/GT hybrid system. The H 2 gas is separated from the outlet mixture gas of SOFC1 anode by employing the advanced ceramic proton membrane technology, and then, it is injected into SOFC2 to continue a new electrochemical reaction. The outlet gas of SOFC1 cathode and the exhaust gas from SOFC2 burn in the afterburner 1. The combustion gas production of the afterburner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Thus, the effects of waste heat source temperature on the bottoming ORC subsystems and fluid selection are of importance to further be investigated. The exhaust temperature is chosen in the range of 500 K to 600 K based on the typical exhaust temperatures found in literature .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effects of waste heat source temperature on the bottoming ORC subsystems and fluid selection are of importance to further be investigated. The exhaust temperature is chosen in the range of 500 K to 600 K based on the typical exhaust temperatures found in literature .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the effects of waste heat source temperature on the bottoming ORC subsystems and fluid selection are of importance to further be investigated. The exhaust temperature is chosen in the range of 500 K to 600 K based on the typical exhaust temperatures found in literature [2,6,9,11,14,[30][31][32][33]. Figure 10 shows the actual thermal efficiency of ORC system with different working fluids when exhaust temperature varies from 500 K to 600 K. It is evident that the effect of the exhaust temperature on the cycle performance strongly depends on the critical point temperature of the working fluids.…”
Section: Resultsmentioning
confidence: 99%
“…Preheated reformate (B) and air (5) participated in the electrochemical reactions in SOFC to generate DC power. Unutilized fuel (C) from SOFC stack was mixed with cathode exhaust air (6), and burned in the post-combustor to further increase the temperature before entering the turbine to generate AC power. The total system's net electrical power was the combination of DC and AC power.…”
Section: Hybrid Sofc/gt Topping Cycle With An External Reformermentioning
confidence: 99%
“…5 Carbon capture could be adopted easily in the SOFC-GT hybrid due to the exhaust gas from SOFC anode is not diluted with nitrogen. 6,7 Recent research demonstrated that this hybrid could maintain high efficiencies during load following and part load operation, which makes it a good fit for distributed energy generation systems and micro-grids. 8,9 Recently, hybrid SOFC/GT systems fueled with natural gas (NG) are gaining increasing attentions all over the world due to the competitive pricing and increasing availability of NG.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the first two reactions are assumed to reach chemical equilibrium since completion is reached very quickly at high temperatures > 600 °C 17, while the electrochemical reaction has a fixed extent to match the given fuel utilization. The equilibrium constants K shift corresponding to the water‐gas shift reaction are calculated as proposed by 19, 20: …”
Section: System Modelmentioning
confidence: 99%